Analysis of Dynamics of Development of Services in Uzbekistan - Sabirov Khasan Nusratovich; Nishonboyeva Nilufar Khasan qizi (Genius Publishing Group, 2022)
This article discusses the current role of the service sector, stages of development, many reforms, advantages and disadvantages of the industry, as well as changes in this area in Uzbekistan, the strategy of reforms and training programs for qualified personnel. many topical issues are covered. In addition, the following article provides information on such necessary and easy-to-use applications. In particular, the activities, popularity, scope, evidence-based diagnosis and other features of the "Abu Bakr ar-Razi med servis" clinic in Kokand, which is based on the unique environment for the population, are briefly described
Keywords: medicine; services; correlation coefficient; regression model